Marine Reservoir Corrections for the Brazilian Northern Coast Using Modern Corals. Issue 2 (13th March 2019) - Oliveira, Maria Isabela; Carvalho, Carla; Macario, Kita; Evangelista, Heitor; Lamounier, Saulo; Hammerschlag, Izabela
ABSTRACT: The Abrolhos bank, in southern Bahia State (BA), is the largest coral reef system in the southwestern Atlantic. It is highly influenced by the Brazil Current (BC), since it is located in the continental shelf. By contrast, Todos os Santos Bay (TSB), in Salvador, capital of Bahia State (BA) has an important coral biodiversity, located in a bay inlet with restricted water circulation. Coral cores were collected in those sites and were analyzed for density band counting and by Th/U dating to estimate growth rates and age. In this work, we present 14 C ages of some of these bands in order to evaluate the marine reservoir effect (MRE) to which the colonies were subjected during growth. It is the first study making use of coral skeleton samples for MRE determination for the Brazilian coast. ΔR was calculated to be –151±23 14 C yr, while that for the TSB was –107±51 14 C yr.